Pengaruh Jumlah Penduduk, Pendidikan, dan Upah Terhadap Pengangguran Terbuka di Jawa Timur - Lestari, Intan; Solihah, Nabilatus; Fina Audilla, Yessiska; Nilasari, Aprillia (Independent: Journal of Economics, 2024)
A high population is a potential source of economic development, but if it is not balanced with job opportunities it will lead to unemployment. This research aims to look at the influence of population, education level, minimum salary on the level of open poverty in East Java 2019 - 2023. This research using a quantitative approach using panel regression analysis methods using the fixed effect model (FEM). The results show that: Through a partial test, population has a positive or insignificant effect on the level of open poverty, education level has a negative and insignificant effect on the level of open poverty, and the minimum wage has a positive and significant effect on open poverty in East Java in 2019 - 2023. Meanwhile Simultaneous tests show that population, education level and salary simultaneously influence the level of open poverty in East Java in 2019 – 2023.